Contributions of Academic Language, Perspective Taking, and Complex Reasoning to Deep Reading Comprehension. Issue 2 (2nd April 2016) - LaRusso, Maria; Kim, Ha Yeon; Selman, Robert; Uccelli, Paola; Dawson, Theo; Jones, Stephanie; Donovan, Suzanne; Snow, Catherine
ABSTRACT: Deep reading comprehension refers to the process required to succeed at tasks defined by the Common Core State Literacy Standards, as well as to achieve proficiency on the more challenging reading tasks in the Program for International Student Assessment (PISA) framework. The purpose of this study was to test the hypothesis that three skill domains not frequently attended to in instruction or in theories of reading comprehension—academic language, perspective taking, and complex reasoning—predict outcomes on an assessment of deep reading comprehension. The Global Integrated Scenario-based Assessment (GISA; O'Reilly, Weeks, Sabatini, Halderman, & Steinberg, 2014 ) is designed to reflect students' abilities to evaluate texts, integrate information from an array of texts, and use textual evidence to formulate a position, all features of deep reading comprehension. We tested the role of academic language, perspective taking, and complex reasoning in explaining variance in end-of-year GISA scores, controlling for beginning-of-year scores and student demographics. All three predictors explained small, but significant, amounts of additional variance. We suggest that these three skill domains deserve greater attention in theories of reading comprehension and in instruction.